2014
DOI: 10.1021/jf500438s
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Alkali-Soluble Heteropolysaccharide from Tetraploid Gynostemma pentaphyllum Makino and Its Potential Anti-inflammatory and Antioxidant Properties

Abstract: A novel polysaccharide (GPP-S), with a molecular mass of 1.2 × 10(6) Da, was isolated from the tetraploid Gynostemma pentaphyllum Makino by alkali extraction followed by purifications using DEAE and Sephacryl S-400 column chromatographies. The monosaccharide composition of GPP-S was determined as rhamnose, arabinose, glucose, and galactose with a molar ratio of 1.00:3.72:19.49:7.82. The structural analysis suggested that the backbone of GPP-S is (1→4)-linked-glucose and (1→6)-linked-galactose with a (1→4,6)-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…[ 19 ]. Pharmacological studies revealed that GP possessed various bioactivities including antioxidation [ 20 ], anti-inflammatory [ 21 ], hypoglycemia [ 22 , 23 ], lipid-lowering [ 24 ], as well as hepatoprotective effects [ 25 ]. Meanwhile, no toxicity were reported at conventional dosage of GP [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ]. Pharmacological studies revealed that GP possessed various bioactivities including antioxidation [ 20 ], anti-inflammatory [ 21 ], hypoglycemia [ 22 , 23 ], lipid-lowering [ 24 ], as well as hepatoprotective effects [ 25 ]. Meanwhile, no toxicity were reported at conventional dosage of GP [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our study showed that PSPPs could enhance the productions of anti‐inflammatory short‐chain fatty acids (SCFAs) by proliferating the growths of SCFA‐producing bacteria and inhibit the relative abundance of inflammation‐related bacteria in normal mice (Tang et al, ). Furthermore, a novel alkali‐soluble heteropolysaccharide from Tetraploid Gynostemma pentaphyllum Makino exhibited potential anti‐inflammatory properties in LPS stimulated macrophages (Niu et al, ). Although many kinds of plant polysaccharides, including water‐ and alkali‐soluble polysaccharides, have been proved to possess anti‐inflammatory effects on LPS treated macrophages, no study has been conducted to examine the anti‐inflammatory effects of PSPPs on activated macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…important indicators. Polysaccharides extracted from Gynostemma pentaphyllum Makino, Ganoderma lucidum, and Agaricus blazei Murill were all observed to have anti-inflammatory property partially due to their inhibitory activity on IL-1␤ gene expression or protein secretion [22][23][24]. The inhibitory effect of PPQN on IL-1␤ secretion was also evaluated in our study (Fig.…”
Section: Inhibitory Effect Of Ppqn On Tnf-˛ Il-6 and Il-1š Ecretionmentioning
confidence: 99%